Simple traumatic elbow dislocations; benefit from early functional rehabilitation: A systematic review with meta-analysis including PRISMA criteria. Issue 44 (5th November 2021) - Schubert, Ilona; Strohm, Peter C.; Maier, Dirk; Zwingmann, Jörn
Abstract: Introduction: Elbow dislocation is the second most frequent joint dislocation after shoulder dislocation. They have a high relevance because they can result in subsequent damage and limitations in range of motion. The treatment options are controversially discussed. The purpose of this systematic review and meta-analysis was to review the literature and analyze the evidence of early functional rehabilitation. Methods: A systematic literature search was performed via Ovid Medline, whereby 1645 publications were identified and evaluated in a stepwise approach. Of these publications 29 met the inclusion criteria of the authors and described simple elbow dislocations in 5765 patients. Data from the studies and subgroups included were initially categorized descriptively in conservative and surgical primary therapies, in immobilizing (immobilization lasting 2 weeks or longer) and free-functional follow-up treatments, and those data were then extracted from each subgroup in absolutes. We then pooled these numbers into descriptive statistics to ensure their comparability. We determined the success rates from the numbers of excellent and good results of the specific used outcome scores. Results: The effect estimate of the conservative therapy's success rate was 84% and for surgical treatment 80% ( P  < .0001). The difference between the immobilizing treatment (78% success rate) and early-function therapy (83% success rate) was significant ( P  = .002). In a subgroup analysis the success rate of conservative and immobilizing therapy was 79%, of conservative and early-functional therapy 91%, of surgical and immobilizing groups' was 77% and of the surgical and early-functional therapies was 93%. The difference among the 4 treatment options was significant ( P  < .0001), as were differences between the 2 conservative groups ( P  < .0001) and between the 2 surgical groups ( P  = .044). Discussion: Conservative therapy is the dominant therapy. Regardless of the primary therapy chosen in simple elbow dislocations: early functional follow-up care seems to be superior to immobilizing therapy with a duration more than 2 weeks.